Transplantation of Mesenchymal Stem Cells: A Potential Adjuvant Therapy for COVID-19 - Zhu, Yingqian; Geng, Shasha; Li, Qingqing; Jiang, Hua (Frontiers in Bioengineering and Biotechnology, 2020)
SARS-CoV-2 (severe acute respiratory syndrome coronavirus-2) is the causative pathogen for COVID-19 (coronavirus disease-2019), which has posed an increasing serious public health threat. However, still there are no approved antiviral agents or vaccines available yet. Mesenchymal stem cells (MSCs) are emerging as a novel promising adjuvant therapy for the attenuation of COVID-19 based on its putative pathogenesis. MSCs may exert anti-inflammatory, immunomodulatory, anti-apoptotic as well as regenerative effects through a series of mechanisms. Remarkably, MSCs may be resistant to virus infection, which is fundamental for the treatment of COVID-19. The beneficial therapeutic effects of MSCs have been preliminarily proved to be safe and efficacious for the treatment of COVID-19 in current clinical trials. This work aims to review the beneficial effects of MSCs in treating ALI/ARDS, which provides novel insight into the potential therapeutic strategies against COVID-19. However, further research is warranted regarding both safety and efficacy of MSCs.